A Framework For Work‐Life Instruments: A Cross‐National Review. Issue 5 (13th May 2014) - Bardoel, E. Anne; De Cieri, Helen
<x xml:space="preserve">Abstract</x> Recently there has been growing attention paid by practitioners to the need for effective measurement of the contribution of work‐life management initiatives to both financial and nonfinancial performance objectives and to organizational effectiveness overall. We review a range of performance indicators, criteria, and indices that are used in a variety of countries to measure the performance of work‐life initiatives. Using insights from research as a theoretical foundation, we present a framework for organizations to use when developing metrics for work‐life measurement that comprise the four dimensions of planning and alignment, customization, supportive culture, and demonstrated value. Finally, we offer recommendations for research and practice related to measurement of work‐life initiatives to assist scholars, managers, employees, and communities. © 2014 Wiley Periodicals, Inc.